The Effect Of Service Quality And Price On Customer Satisfaction At Cv. Abadi Steel Lahat - Jesi Monica; Mujari Mujari; Darwin Kesuma (Universitas Dehasen Bengkulu, 2026)
The purpose of this study was to determine the effect of service quality and price on customer satisfaction at CV. Abadi Steel Lahat. The results showed that (1) service quality has a significant partial effect on customer satisfaction at CV. Abadi Steel Lahat, as evidenced by the calculated t-value > t-table (7.031 > 1.988). (2) price has a significant partial effect on customer satisfaction at CV. Abadi Steel Lahat, as evidenced by the calculated t-value > t-table (3.224 > 1.988). (3) service quality and price have a significant simultaneous effect on customer satisfaction at CV. Abadi Steel Lahat, as evidenced by the calculated f-value > f-table (58.389 > 3.953), with a significance value lower than the significance level (a) of 0.05 (0.000 < 0.05).